Peripheral Tangible Interaction - Edge, Darren; Blackwell, Alan F. (S. Bakker, D. Hausen & T. Selker (Eds), Peripheral Interaction: Challenges and Opportunities for HCI in the Periphery of Attention, 2016)
Much of our everyday interaction in the physical world is peripheral – many of the objects that reside on the periphery of our awareness also require or allow actions in the periphery of our attention, as we briefly touch, handle, move, or avoid them. When these objects are digitally augmented, computational operations extend beyond dedicated display screens, and leverage our capacity for occasional and low-attention interactions in the physical world. The research presented in this chapter analyzes this phenomenon of peripheral tangible interaction. Understanding the use qualities of the resulting tangible notations is critical to the design of interfaces aiming to facilitate peripheral interaction. We discuss when and how to design for peripheral tangible interaction based on systematic analyses of user activities and of system qualities. We illustrate both through a case study: the design of ShuffleBoard, a tangible interface for desk work in an office context, in which interactive surfaces and digitally-augmented physical tokens support interaction with significant tasks, documents, and people, alongside and concurrently with focal workstation tasks.